(untitled) (The Peerian Journal, 2023)
This article describes in detail the dialectic of the national idea and national ideology, the main universal principles on which the national idea is based, the independence of the country, the most powerful and noble thoughts in society, the role of public organizations in the formation of the national idea and its importance.